S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material as well as preparation method and application thereof
By growing the covalent frame material on the surface of titanium dioxide, the S -type heterogeneous knot is constructed, and the S -type heterogeneous knot is constructed, and the problem of only the problem of only ultraviolet light catalytic materials that can only be stimulated by ultraviolet light and the significant improvement of photocatalytic performance.
Patent Information
- Application Number
- CN202411390670.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-24
AI Technical Summary
Existing photocatalytic materials such as titanium dioxide can only be excited by ultraviolet light due to their large bandwidth, which limits their further development and use in the field of photocatalytics.
By growing covalent organic framework materials on the surface of titanium dioxide hollow spheres, an S-shaped heterojunction is constructed to expand the photoresponse range to the visible light range and improve photocatalytic performance.
The photocatalytic performance is significantly improved, the photoresponse range is expanded, the material can effectively utilize visible light, and the activity of photocatalytic hydrogen peroxide production is improved.
Smart Images

Figure CN119346180A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic material synthesis, and in particular to an S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material and a preparation method and application thereof. Background Art
[0002] Hydrogen peroxide is an important inorganic chemical product, which is widely used in the textile industry, pharmaceutical industry, paper industry, chemical industry and wastewater treatment industry. Anthraquinone method is a commonly used process for producing hydrogen peroxide. This method is widely used in industrial production. The hydrogen peroxide produced by this method accounts for more than 95% of the total hydrogen peroxide production. However, this method has some disadvantages: 1) The required production line is large and energy-consuming. 2) The organic solvents used in the production process are highly toxic. 3) Organic by-products and a large amount of wastewater will be produced during the production process, polluting the environment. 4) The precious metal catalysts required for production are relatively expensive. Therefore, it is necessary to explore an economical, environmentally friendly and safe method for preparing hydrogen peroxide. People have tried to directly synthesize hydrogen peroxide with hydrogen and oxygen, but because the mixed gas of hydrogen and oxygen has the possibility of explosion, this method is not suitable for large-scale production of hydrogen peroxide. In addition, some people use electrolysis to produce hydrogen peroxide. This method uses platinum as an anode and lead or graphite as a cathode to electrolyze a saturated ammonium hydrogen sulfate solution into ammonium persulfate, and then hydrolyze it with dilute sulfuric acid to obtain hydrogen peroxide. However, this method consumes a lot of energy and is not suitable for large-scale production. In recent years, the production of hydrogen peroxide by solar-driven photocatalysis has attracted great interest due to its green, environmentally friendly, safe and economical characteristics. This technology can utilize the electrons and holes generated by photocatalysts under sunlight to produce hydrogen peroxide using oxygen and water as raw materials.
[0003] Titanium dioxide is widely used in the field of photocatalysis because of its advantages such as high photocatalytic activity, low price, stable properties and non-toxicity. However, due to its large bandgap (3.2eV), it can only be excited by ultraviolet light, which limits the further development and use of titanium dioxide. Therefore, broadening the absorption range of sunlight is the key problem that titanium dioxide materials need to solve at present. Covalent organic framework materials (COFs) have become a very promising photocatalytic material due to their excellent optical properties, easily customizable chemical structure, narrow bandgap and excellent chemical stability. However, they also have shortcomings such as rapid recombination of photogenerated electrons and holes and large energy loss during charge migration. To solve these problems, people have tried many methods, such as functional group modification, heteroatom doping and construction of heterojunctions, to improve the catalytic performance of photocatalytic materials. Summary of the invention
[0004] The technical problem that the present invention aims to solve is to provide an S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material and its preparation method and application in view of the above-mentioned deficiencies in the prior art. A layer of covalent organic framework material is grown on the surface of the titanium dioxide hollow sphere to construct an S-type heterogeneous material to improve the photocatalytic performance. The light response range of the composite photocatalytic material is expanded to the visible light range, which significantly improves the photocatalytic performance.
[0005] An S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material, which consists of titanium dioxide hollow spheres and covalent organic frameworks uniformly distributed on the surfaces of the titanium dioxide hollow spheres, wherein the titanium dioxide hollow spheres and the covalent organic frameworks form an S-type heterojunction, and the titanium dioxide is anatase type.
[0006] Furthermore, the mass ratio of the covalent organic framework to the hollow titanium dioxide spheres is 1 to 20:50.
[0007] Furthermore, the diameter of the hollow titanium dioxide sphere is 500-600 nm.
[0008] The method for preparing the above-mentioned S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material is characterized by comprising the following steps:
[0009] S1. Preparation of silicon dioxide: tetraethyl orthosilicate is slowly added dropwise to a mixed solution of ethanol and ammonia water, and after sufficient reaction at room temperature, the generated precipitate is washed and dried to obtain silicon dioxide balls;
[0010] S2, preparation of titanium dioxide-silicon dioxide core-shell structure: ultrasonically disperse the silicon dioxide balls in S1 in anhydrous ethanol, add a small amount of ammonia water after uniform dispersion, add tetrabutyl titanate dropwise after stirring, and react fully after the addition is complete. After the reaction is completed, wash and dry the precipitate, and anneal it to obtain the titanium dioxide-silicon dioxide core-shell structure;
[0011] S3, titanium dioxide-silicon dioxide core-shell structure material surface-modified with polyvinyl pyrrolidone and polyethyleneimine: the titanium dioxide-silicon dioxide core-shell structure material in S2 is ultrasonically dispersed in anhydrous ethanol to obtain a mixed solution, and a modification liquid with a volume ratio of 1:1 is dripped into the mixed solution. After sufficient reaction, the modified titanium dioxide-silicon dioxide emulsion is obtained after washing;
[0012] The modified liquid is a mixed solution of polyvinyl pyrrolidone, polyethyleneimine and ethanol solution;
[0013] S4. Preparation of covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material: dissolve 1,3,5-tri(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde in a mixed solution of 1,4-dioxane and n-butanol, and obtain a transparent solution by ultrasonication; add the titanium dioxide-silicon dioxide emulsion in S3 dropwise to the above transparent solution, disperse evenly, and react in an oil bath. After the reaction, an initial photocatalytic material is obtained, which is placed in hydrofluoric acid to etch away silicon dioxide to obtain a covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material.
[0014] Furthermore, in S1, the volume ratio of the ammonia water to the ethanol is 1:2-5, the volume ratio of the tetraethyl orthosilicate to the mixed solution of the ethanol and the ammonia water is 1-3:50, and the stirring time is 0.5-3h.
[0015] Further, in S2, the mass volume ratio of the silica spheres to the anhydrous ethanol is 1-3 g:750 mL;
[0016] The volume ratio of the aqueous ammonia to the anhydrous ethanol is 1 to 4:300;
[0017] The volume ratio of the tetrabutyl titanate to the anhydrous ethanol is 1 to 2:75;
[0018] The drying temperature is 60°C and the drying time is 6 to 12 hours;
[0019] The annealing conditions are calcination at 400-600°C for 1-3h in an air atmosphere, and the heating rate during annealing is 5°C / min.
[0020] Further, in S3, the mass volume ratio of the titanium dioxide-silicon dioxide core-shell structure material to the anhydrous ethanol is 1-3 g:50 mL;
[0021] In the modified liquid, the mass volume ratio of the polyvinyl pyrrolidone, the polyethylene imine and the anhydrous ethanol is 1g:1g:25mL;
[0022] The volume ratio of the mixed solution to the modified solution is 1:1;
[0023] The time condition for the modification treatment is 24h.
[0024] Further, in S4, the volume ratio of the 1,4-dioxane to the n-butanol is 1:0.5-2; the mass volume ratio of the titanium dioxide-silicon dioxide emulsion to the 1,4-dioxane-n-butanol mixed solution is 1 g:20 mL;
[0025] The mass ratio of the 1,3,5-tris(4-aminophenyl)benzene and the 2,5-dimethoxyterephthalaldehyde to the titanium dioxide-silicon dioxide emulsion is 11:9:100-1000;
[0026] The mass fraction of the hydrofluoric acid is 1 to 3%;
[0027] The mass volume ratio of the initial photocatalytic material to the hydrofluoric acid solution is 1-5 g:250 mL;
[0028] The temperature condition of the oil bath reaction is 60-90° C., the time condition is 48 h to 72 h, and the hydrofluoric acid etching reaction time is 10 to 20 min.
[0029] Furthermore, in S4, the material after the hydrofluoric acid etching treatment is successively subjected to precipitation centrifugation treatment, washed with tetrahydrofuran and acetone, and then dried at a temperature of 60° C. for 6 to 12 hours to obtain a covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material.
[0030] The above-mentioned S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material is used in the photocatalytic production of hydrogen peroxide.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material provided by the present invention is a double-layer hollow sphere structure obtained by growing a covalent organic framework on the surface of a titanium dioxide-silicon dioxide core-shell structure as a template and etching with hydrofluoric acid. The structure is stable and has a large specific surface area, which can provide more active sites for photocatalytic reactions. At the same time, the ultra-thin shell structure is beneficial to shorten the diffusion length of photogenerated electrons and holes from the inside to the surface, so as to enhance the separation of photogenerated electrons and holes and promote surface redox reactions. In addition, the refraction and reflection of light inside the hole structure can improve the utilization rate of solar energy by the material, and further enhance the activity of photocatalytic production of hydrogen peroxide.
[0033] 2. In the photocatalytic material of the present invention, the covalent organic framework and titanium dioxide form an S-type heterojunction, the covalent organic framework serves as a reduction photocatalyst, and titanium dioxide serves as an oxidation photocatalyst. The reduction photocatalyst has a higher Fermi level than the oxidation photocatalyst. After the two are combined, due to the difference in Fermi level, the electrons from the reduction photocatalyst are transferred to the oxidation photocatalyst. Driven by the band bending and the built-in electric field, the photogenerated holes will accumulate in the valence band of the oxidation photocatalyst, while the photogenerated electrons will remain in the conduction band of the reduction photocatalyst. Therefore, the S-type heterojunction can promote the separation of photogenerated electrons and holes, and is suitable for the photocatalytic production of hydrogen peroxide.
[0034] 3. The preparation method of the present invention prepares a titanium dioxide-silicon dioxide core-shell structure by a template method, then modifies the titanium dioxide-silicon dioxide surface, grows a covalent organic framework on the surface, and thus prepares a covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material. The present invention is simple to operate, has low raw material prices, does not require complex equipment, and has a safe and non-toxic product, so it has good industrial production prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope photograph of the covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material prepared in Example 1 of the present invention;
[0036] Figure 2 This is a high-resolution transmission electron microscopy photograph of the covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material prepared in Example 1 of the present invention;
[0037] Figure 3 X-ray diffraction patterns of the materials prepared in Example 1 and Comparative Examples 1-2 of the invention;
[0038] Figure 4 The ultraviolet-visible diffuse emission absorption spectra of the materials prepared in Example 1 and Comparative Examples 1-2 of the present invention;
[0039] Figure 5 This is a performance diagram of photocatalytic production of hydrogen peroxide of the materials prepared in Example 1 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION
[0040] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not indicated, they are all conventional products that can be obtained commercially.
[0041] The first object of the present invention is to provide an S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material, which is composed of titanium dioxide hollow spheres and covalent organic frameworks uniformly distributed on the surfaces of the titanium dioxide hollow spheres, wherein the titanium dioxide is anatase type, and the diameter of the titanium dioxide hollow spheres is 500-600nm; the mass ratio of the covalent organic framework to the titanium dioxide hollow spheres is 1-20:50, and the titanium dioxide is anatase type.
[0042] The second object of the present invention is to provide a method for preparing the above-mentioned S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material, the steps of which are as follows:
[0043] 1) Preparation of silicon dioxide: Tetraethyl orthosilicate is slowly added dropwise to a mixed solution of ethanol and ammonia water. After sufficient reaction at room temperature, the generated precipitate is washed and dried to obtain silicon dioxide spheres.
[0044] In this step, the volume ratio of ammonia water to ethanol is 1:2-5, the volume ratio of tetraethyl orthosilicate to the above-mentioned mixed solution is 1-3:50, and the stirring time is 0.5-3h. When the proportion of ammonia water is small, the surface of the produced silica spheres will be irregular, and too little or too much tetraethyl orthosilicate will make the obtained silica spheres too small or too large. Preferably, the volume ratio of ammonia water to ethanol is 1:3-4, and the volume ratio of tetraethyl orthosilicate to the above-mentioned mixed solution is 2-3:50.
[0045] 2) Preparation of titanium dioxide-silicon dioxide core-shell structure: Ultrasonic dispersion of the silicon dioxide spheres in step 1) in anhydrous ethanol, adding a small amount of ammonia water after uniform dispersion, adding tetrabutyl titanate dropwise after stirring completely, and reacting fully after the addition is complete. After the reaction is completed, the precipitate is washed and dried, and annealed in a muffle furnace to obtain a titanium dioxide-silicon dioxide core-shell structure.
[0046] In this step, the mass volume ratio of silica spheres to anhydrous ethanol is 1 to 3 g: 750 mL; the volume ratio of ammonia water to anhydrous ethanol is 1 to 4: 300; the volume ratio of tetrabutyl titanate to anhydrous ethanol is 1 to 2: 75; the annealing condition is calcined at 400 to 600 ° C for 1 to 3 hours in an air atmosphere. Excessively high concentrations of ammonia water will promote the rapid hydrolysis of tetrabutyl titanate, resulting in an uneven surface of the titanium dioxide spheres. Preferably, the mass volume ratio of silica to anhydrous ethanol is 1 to 2 g: 750 mL, the volume ratio of ammonia water to anhydrous ethanol is 1 to 2: 300, and the annealing condition is calcined at 550 ° C for 1 to 3 hours in an air atmosphere.
[0047] 3) Polyvinyl pyrrolidone and polyethyleneimine modified titanium dioxide-silicon dioxide core-shell structure material: ultrasonically disperse the titanium dioxide-silicon dioxide core-shell structure material in step 2) in anhydrous ethanol to obtain a mixed solution, drop a modified liquid into the mixed solution, and after sufficient reaction, wash with ethanol and n-butanol to obtain a modified titanium dioxide-silicon dioxide emulsion, and disperse it in n-butanol for storage; wherein the modified liquid is a mixed solution of polyvinyl pyrrolidone, polyethyleneimine and ethanol solution;
[0048] In this step, the mass volume ratio of titanium dioxide-silicon dioxide core-shell structure material and anhydrous ethanol in step 3) is 1-3g:50ml; in the modified liquid, the mass volume ratio of polyvinyl pyrrolidone, polyethyleneimine and anhydrous ethanol is 1g:1g:25mL; the volume ratio of the mixed solution to the modified liquid is 1:1.
[0049] 4) Preparation of covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material: 1,3,5-tri(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde were dissolved in a mixed solution of 1,4-dioxane and n-butanol, and ultrasonication was performed to obtain a transparent solution;
[0050] The modified titanium dioxide-silicon dioxide emulsion in step 3) is added dropwise to the above transparent solution, and after being uniformly dispersed, reacted under oil bath conditions. After the reaction is completed, an initial photocatalytic material is obtained, which is placed in hydrofluoric acid to etch away silicon dioxide, thereby obtaining a covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material.
[0051] In this step, the volume ratio of 1,4-dioxane to n-butanol is 1:0.5-2; the mass volume ratio of titanium dioxide-silicon dioxide to 1,4-dioxane-n-butanol mixed solution is 1g:20ml; the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:100-1000; the mass fraction of hydrofluoric acid is 1-3%. Preferably, the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200-400.
[0052] In this step, the mass volume ratio of the initial photocatalytic material to the hydrofluoric acid solution is 1-5 g: 250 mL. Preferably, the mass volume ratio of the initial photocatalytic material to the hydrofluoric acid solution is 1 g: 250 mL.
[0053] In this step, the oil bath reaction condition in step 4) is 60-90°C, and the oil bath reaction time is 48h-72h. Preferably, the oil bath reaction condition is 80°C, and the oil bath reaction time is 72h.
[0054] In this step, the hydrofluoric acid etching reaction time in step 4) is 10 to 20 minutes. Preferably, the hydrofluoric acid etching reaction time is 10 minutes.
[0055] The third object of the present invention is to provide the use of the above covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in photocatalytic production of hydrogen peroxide.
[0056] Comparative Example 1
[0057] The preparation method of titanium dioxide hollow spheres is as follows:
[0058] 1) Preparation of silicon dioxide: Tetraethyl orthosilicate is used as a silicon source, and is slowly added dropwise to a mixed solution of ethanol and ammonia water. After stirring at room temperature for 1 hour, the resulting precipitate is washed and dried to obtain silicon dioxide spheres. The volume ratio of ammonia water to ethanol is 3:10, and the volume ratio of tetraethyl orthosilicate to the mixed solution is 1:25.
[0059] 2) Preparation of titanium dioxide-silicon dioxide core-shell structure: Ultrasonic dispersion of silicon dioxide balls in step 1) in anhydrous ethanol, adding a small amount of ammonia water after uniform dispersion, adding tetrabutyl titanate dropwise after complete stirring, reacting fully after complete addition, washing and drying the precipitate after the reaction, and annealing in a muffle furnace to obtain a titanium dioxide-silicon dioxide core-shell structure. The mass volume ratio of silicon dioxide balls to anhydrous ethanol is 1g:750mL; the volume ratio of ammonia water to anhydrous ethanol is 1:300; the volume ratio of tetrabutyl titanate to anhydrous ethanol is 1:75, and the annealing conditions are calcination at 550℃ for 2h in air atmosphere, and the heating rate during annealing is 5℃ / min.
[0060] 3) Preparation of hollow titanium dioxide spheres: The titanium dioxide-silicon dioxide core-shell structure in step 2) is etched with a hydrofluoric acid solution to obtain a titanium dioxide composite hollow sphere photocatalytic material. The mass fraction of hydrofluoric acid in the hydrofluoric acid solution is 1%, and the amount ratio of the hydrofluoric acid solution to the titanium dioxide-silicon dioxide core-shell structure is 1g:250mL.
[0061] Comparative Example 2
[0062] The steps of preparing the covalent organic framework are as follows:
[0063] 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde are dissolved in a mixed solution of 1,4-dioxane-n-butanol, and a transparent solution is obtained by ultrasonication. The mixture is reacted in an oil bath at 80°C for 72 hours. After the reaction is completed, the covalent organic framework is obtained by washing and drying. Among them, the volume ratio of 1,4-dioxane to n-butanol in the mixed solution of 1,4-dioxane-n-butanol is 1:1, and the molar ratio of 1,3,5-tris(4-aminophenyl)benzene to 2,5-dimethoxyterephthalaldehyde is 2:3.
[0064] Example 1
[0065] The preparation method of S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material comprises the following steps:
[0066] 1) Preparation of silicon dioxide: Tetraethyl orthosilicate is used as a silicon source, and is slowly added dropwise to a mixed solution of ethanol and ammonia water. After stirring at room temperature for 1 hour, the generated precipitate is washed and dried to obtain silicon dioxide spheres. The volume ratio of ammonia water to ethanol is 1:3, and the volume ratio of tetraethyl orthosilicate to the mixed solution is 1:25.
[0067] 2) Preparation of titanium dioxide-silicon dioxide core-shell structure: Ultrasonic dispersion of silicon dioxide balls in step 1) in anhydrous ethanol, adding a small amount of ammonia water after uniform dispersion, adding tetrabutyl titanate dropwise after complete stirring, reacting fully after complete addition, washing and drying the precipitate after the reaction, and annealing in a muffle furnace to obtain a titanium dioxide-silicon dioxide core-shell structure. The mass volume ratio of silicon dioxide balls to anhydrous ethanol is 1g:750mL; the volume ratio of ammonia water to anhydrous ethanol is 1:300; the volume ratio of tetrabutyl titanate to anhydrous ethanol is 1:75, and the annealing conditions are calcination at 550℃ for 2h in air atmosphere, and the heating rate during annealing is 5℃ / min.
[0068] 3) Surface modification of titanium dioxide-silicon dioxide core-shell structure material by polyvinyl pyrrolidone and polyethyleneimine: Ultrasonic dispersion of titanium dioxide-silicon dioxide core-shell structure material in step 2) in anhydrous ethanol to obtain a mixed solution, and then dripping a modification liquid with a volume ratio of 1:1 into the mixed solution. After sufficient reaction, washing with ethanol and n-butanol, and dispersing in n-butanol for storage. Among them, the modification liquid is a mixed solution of polyvinyl pyrrolidone, polyethyleneimine and ethanol solution, and the mass volume ratio of titanium dioxide-silicon dioxide core-shell structure material to anhydrous ethanol is 1g:50mL; the mass volume ratio of polyvinyl pyrrolidone and polyethyleneimine to anhydrous ethanol is 1g:1g:25mL.
[0069] 4) Preparation of covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material: dissolving 1,3,5-tri(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde in a mixed solution of 1,4-dioxane and n-butanol, and obtaining a transparent solution by ultrasonication; dropping the modified titanium dioxide-silicon dioxide emulsion in step 3) into the above transparent solution, uniformly dispersing the modified titanium dioxide-silicon dioxide emulsion, and reacting it in an oil bath at 80°C for 72 hours. After the reaction, the reaction product is successively subjected to precipitation centrifugation treatment, washed with tetrahydrofuran and acetone, and then dried at 60°C for 6 to 12 hours to obtain an initial catalyst material; etching away the silicon dioxide in the initial catalyst material with hydrofluoric acid, and the hydrofluoric acid etching reaction time is 10 minutes to obtain a covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material. Among them, the volume ratio of 1,4-dioxane to n-butanol is 1:1; the mass volume ratio of titanium dioxide-silicon dioxide to 1,4-dioxane-n-butanol mixed solution is 1g:20mL; the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:400; the mass fraction of hydrofluoric acid is 1%, and the mass volume ratio of the initial photocatalytic material to the hydrofluoric acid solution is 1g:250mL.
[0070] Figure 1This is a scanning electron microscope photo of the covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material prepared in Example 1. Figure 1 It can be seen that the diameter of the hollow sphere structure composite photocatalytic material is between 500 and 600 nm.
[0071] Figure 2 This is a high-resolution transmission electron microscope photograph of the covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material prepared in Example 1. Figure 2 The titanium dioxide and covalent organic framework components at the edge of the composite material can be clearly seen; further, the lattice fringes of titanium dioxide can be observed, with a fringe spacing of 0.36nm.
[0072] Figure 3 The X-ray diffraction patterns of the materials obtained in Example 1 (TC5) and Comparative Examples 1 (TiO2) and 2 (TD-COF) are shown in Figure 1. The diffraction peaks of pure titanium dioxide hollow spheres and covalent organic frameworks completely correspond to their standard cards (PDF#78-2486) and simulated peaks; in addition to the diffraction peaks of titanium dioxide, the diffraction peaks of the covalent organic framework also appear in the titanium dioxide-covalent organic framework composite photocatalyst, confirming the successful synthesis of the composite material (the composite material is abbreviated as TC5 in the figure, and the covalent organic framework is abbreviated as TD-COF).
[0073] Figure 4 The UV-visible diffuse reflectance absorption spectra of the materials obtained in Example 1 (TC5) and Comparative Examples 1 (TiO2) and 2 (TD-COF) are shown in the figure. As can be seen from the figure, when titanium dioxide and the covalent organic framework construct a heterojunction photocatalyst, its light absorption in the visible light region is enhanced (the composite material is abbreviated as TC5 and the covalent organic framework is abbreviated as TD-COF in the figure).
[0074] Photocatalytic production of hydrogen peroxide test:
[0075] The photocatalytic production of hydrogen peroxide experiment was carried out in a sealed and oxygen-filled 100 mL glass flask. A 300 W xenon lamp with a wavelength range of 320 to 780 nm was used as the light source. First, 10 mg of the sample was dispersed in 40 mL of a 10 vol% ethanol aqueous solution. Before irradiation, the suspension was passed through O2 for 30 min to achieve O2 saturation. During the photocatalytic production of hydrogen peroxide, 1 mL of the solution was extracted from the solution every 15 min and filtered with a 0.45 μm filter to obtain a transparent solution. Subsequently, 1 mL of 0.1 M potassium hydrogen phthalate and 1 mL of 0.4 M potassium iodide aqueous solution were added and allowed to stand for 30 min. The concentration of hydrogen peroxide was tested using a UV spectrophotometer.
[0076] The hydrogen peroxide production activity of the photocatalyst was calculated by the following formula:
[0077]
[0078] Figure 5 This is a comparison of the photocatalytic performance of producing hydrogen peroxide of the materials obtained in Example 1 (TC5) and Comparative Examples 1 (TiO2) and 2 (TD-COF) (the composite material is abbreviated as TC5, and the covalent organic framework is abbreviated as TD-COF). As can be seen from the figure, the titanium dioxide-covalent organic framework composite photocatalyst exhibits the best performance, with a hydrogen peroxide generation rate of 3.8mmolg -1 h -1 .
[0079] Example 2
[0080] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0081] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200; and the mass volume ratio of the initial photocatalytic material to the hydrofluoric acid solution is 2 g:250 mL.
[0082] Example 3
[0083] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0084] In step 1), the volume ratio of aqueous ammonia to ethanol is 1:4.
[0085] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200.
[0086] Example 4
[0087] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0088] In step 1), the produced precipitate is washed and dried after stirring at room temperature for 0.5 h.
[0089] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200, and the mass volume ratio of the initial photocatalytic material to the hydrofluoric acid solution is 3g:250mL.
[0090] Example 5
[0091] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0092] In step 1), the volume ratio of tetraethyl orthosilicate to the mixed solution is 3:50.
[0093] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200.
[0094] Example 6
[0095] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0096] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200.
[0097] Example 7
[0098] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0099] In step 2), the annealing condition is calcination at 400° C. for 2 h in air atmosphere.
[0100] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200.
[0101] Example 8
[0102] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0103] In step 2), the mass volume ratio of the silica spheres to the anhydrous ethanol is 2 g:750 mL.
[0104] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200, and the mass volume ratio of the initial photocatalytic material to the hydrofluoric acid solution is 2g:250mL.
[0105] Example 9
[0106] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0107] In step 2), the volume ratio of aqueous ammonia to anhydrous ethanol is 2:300.
[0108] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200, and the mass volume ratio of the initial photocatalytic material to the hydrofluoric acid solution is 3g:250mL.
[0109] Example 10
[0110] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0111] In step 2), the volume ratio of tetrabutyl titanate to anhydrous ethanol is 2:75.
[0112] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200.
[0113] Embodiment 11
[0114] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0115] In step 3), the mass volume ratio of the titanium dioxide-silicon dioxide core-shell structure material to anhydrous ethanol is 2g:50mL.
[0116] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200.
[0117] Example 12
[0118] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0119] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200.
[0120] Example 13
[0121] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0122] In step 4), the mass ratio of the 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:200; and the mass fraction of the hydrofluoric acid is 3%.
[0123] Embodiment 14
[0124] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0125] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:100; and the mass fraction of the hydrofluoric acid is 3%.
[0126] Embodiment 15
[0127] The preparation method of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material in this embodiment is the same as the preparation method of Example 1 except for the following differences, and the other preparation conditions are the same:
[0128] In step 2), the mass volume ratio of the silica spheres to the anhydrous ethanol is 3 g:750 mL.
[0129] In step 3), the mass volume ratio of the titanium dioxide-silicon dioxide core-shell structure material to anhydrous ethanol is 3g:50mL.
[0130] In step 4), the mass ratio of 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde to titanium dioxide-silicon dioxide is 11:9:1000; the mass fraction of hydrofluoric acid is 3%, and the mass volume ratio of the initial photocatalytic material to the hydrofluoric acid solution is 1g:50mL.
[0131] For matters not mentioned above, the prior art applies.
[0132] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. An S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material, characterized in that: The photocatalytic material consists of titanium dioxide hollow spheres and a covalent organic framework uniformly distributed on the surface of the titanium dioxide hollow spheres, wherein the titanium dioxide hollow spheres and the covalent organic framework form an S-type heterojunction.
2. The S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material according to claim 1, characterized in that: The mass ratio of the covalent organic framework to the titanium dioxide hollow sphere is 1 to 20:
50.
3. The S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material according to claim 1, characterized in that: The diameter of the titanium dioxide hollow sphere is 500-600nm.
4. A method for preparing the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material according to any one of claims 1 to 3, characterized in that: The specific steps include: S1. Preparation of silicon dioxide: tetraethyl orthosilicate is slowly added dropwise to a mixed solution of ethanol and ammonia water, and after sufficient reaction at room temperature, the generated precipitate is washed and dried to obtain silicon dioxide balls; S2, preparation of titanium dioxide-silicon dioxide core-shell structure: ultrasonically disperse the silicon dioxide balls in S1 in anhydrous ethanol, add a small amount of ammonia water after uniform dispersion, add tetrabutyl titanate dropwise after stirring, and react fully after the addition is complete. After the reaction is completed, wash and dry the precipitate, and anneal it to obtain the titanium dioxide-silicon dioxide core-shell structure; S3, titanium dioxide-silicon dioxide core-shell structure material surface-modified with polyvinyl pyrrolidone and polyethyleneimine: the titanium dioxide-silicon dioxide core-shell structure material in S2 is ultrasonically dispersed in anhydrous ethanol to obtain a mixed solution, and a modified liquid is dripped into the mixed solution. After sufficient reaction, the modified titanium dioxide-silicon dioxide emulsion is obtained after washing; The modified liquid is a mixed solution of polyvinyl pyrrolidone, polyethyleneimine and ethanol solution; S4. Preparation of covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material: dissolve 1,3,5-tri(4-aminophenyl)benzene and 2,5-dimethoxyterephthalaldehyde in a mixed solution of 1,4-dioxane and n-butanol, and obtain a transparent solution by ultrasonication; add the titanium dioxide-silicon dioxide emulsion in S3 dropwise to the above transparent solution, disperse evenly, and react in an oil bath. After the reaction, an initial photocatalytic material is obtained, which is placed in hydrofluoric acid to etch away silicon dioxide to obtain a covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material.
5. The preparation method according to claim 4, characterized in that: In S1, the volume ratio of the ammonia water to the ethanol is 1:2-5, the volume ratio of the tetraethyl orthosilicate to the mixed solution of the ethanol and the ammonia water is 1-3:50, and the stirring time is 0.5-3h.
6. The preparation method according to claim 4, characterized in that: In S2, the mass volume ratio of the silica spheres to the anhydrous ethanol is 1-3 g:750 mL; The volume ratio of the aqueous ammonia to the anhydrous ethanol is 1 to 4:300; The volume ratio of the tetrabutyl titanate to the anhydrous ethanol is 1 to 2:75; The drying temperature is 60°C and the drying time is 6 to 12 hours; The annealing conditions are calcination at 400-600°C for 1-3h in an air atmosphere, and the heating rate during annealing is 5°C / min.
7. The preparation method according to claim 4, characterized in that: In S3, the mass volume ratio of the titanium dioxide-silicon dioxide core-shell structure material to the anhydrous ethanol is 1-3 g:50 mL; In the modified liquid, the mass volume ratio of the polyvinyl pyrrolidone, the polyethylene imine and the anhydrous ethanol is 1g:1g:25mL; The volume ratio of the mixed solution to the modified solution is 1:1; The time condition for the modification treatment is 24h.
8. The preparation method according to claim 4, characterized in that: In S4, the volume ratio of the 1,4-dioxane to the n-butanol is 1:0.5-2; the mass volume ratio of the titanium dioxide-silicon dioxide emulsion to the 1,4-dioxane-n-butanol mixed solution is 1 g:20 mL; The mass ratio of the 1,3,5-tris(4-aminophenyl)benzene and the 2,5-dimethoxyterephthalaldehyde to the titanium dioxide-silicon dioxide emulsion is 11:9:100-1000; The mass fraction of the hydrofluoric acid is 1 to 3%; The mass volume ratio of the initial photocatalytic material to the hydrofluoric acid solution is 1-5 g:250 mL; The temperature condition of the oil bath reaction is 60-90° C., the time condition is 48 h to 72 h, and the hydrofluoric acid etching reaction time is 10 to 20 min.
9. The preparation method according to claim 4, characterized in that: In S4, the modified titanium dioxide-silicon dioxide emulsion is added dropwise to the above transparent solution, and reacted under oil bath conditions after being uniformly dispersed. The reaction product is successively subjected to precipitation and centrifugation treatments, washed with tetrahydrofuran and acetone, and then dried at 60°C for 6 to 12 hours to obtain an initial catalyst material.
10. Use of the S-type covalent organic framework-titanium dioxide composite hollow sphere photocatalytic material according to any one of claims 1 to 3 in photocatalytic production of hydrogen peroxide.
Citation Information
Cited By
Preparation method and enzyme catalysis application of porous framework-like hollow microspheres based on microemulsion polymerization method
CN119978526A